Internal Larval Morphology of Two Species of Shining Leaf Frogs (Anura: Phyllomedusidae: Phasmahyla) - Santos Dias, Pedro Henrique dos; Mongin-Aquino, Marcelle; Vera Candioti, Florencia; Pauline Telles de Carvalho-e-Silva, Ana Maria; Baeta, Dello [UNESP] (Soc Brasileira Herpetologia, 2018)
We describe the buccal cavity and chondrocranial morphology of Phasmahyla cruzi tadpoles in comparison to P. guttata. We also provide a review of some characters for larval phyllomedusids and discuss some evolutionary aspects related to the funnel-mouthed configuration. Our discussion highlights that several characters evolved independently in several taxa with umbelliform oral discs. Nevertheless, we suggest that the dorsal orientation of the suprarostral cartilage and the presence of a prenarial ridge on the buccal roof may represent synapomorphic character states for the genus Phasmahyla.
Keywords: Buccal cavity; Chondrocranium; Neustonic tadpoles; Phasmahyla cruzi; Phasmahyla guttata; Umbelliform oral disc